Emergência, movimento e deslocamento da disciplinarização da análise de discurso no RS - Martins, Taís da Silva (2008)
In this work, we propose a reflection regarding disciplinarization process of Discourse Analysis (DA) in Rio Grande do Sul (RS). In order to do this, we are based on the methodological and theoretical principles of History of the Linguistic Ideas (HIL) which make possible to us circumscribe a incursion through documentary archives that materialize the trajectory of DA since the emergency of this discipline in the curriculums of PUCRS and UFRGS Post-graduate Programs in Languages. Our objective is to understand the movements, displacements and unchangings that constitute the historicity of DA in what it concerns to the designations received in curricular grades of these Programs by this field of knowledge. The archive of our research comprises data and facts related to a History of Linguistics in Language Courses in Brazil since is it is inside this discipline that, in Brazil, DA is institutionalized, and also for a set of institutional documents, such as: annual, daily reports of classes, programs, course schedules and bibliographies of the discipline. The analysis of these texts lead us to make a network of academic-intellectuals relations that embodied DA in RS. From the journey through out the archives we had pointed what concepts, what theoreticians, what subjects mobilize and are mobilized in a discipline that is politically designed as DA as well as it is renamed in other ways and not less politically.